The Formula for Making Seruit (Local Food) Based on Snakehead Fish as a Food Source of High Protein - Bertalina, Bertalina; Sudarmi, Sudarmi; Indriyani, Reni (Poltekkes Kemenkes Tanjung Karang, 2023)
There are many traditional fish dishes, including steamed, fried, boiled, then mixed with shrimp paste/sambal/tempoyak/mango sauce/pineapple sauce and topped with various cooked vegetables/fresh vegetables. Protein requirements ideally, teenage boys need 70 to 75 grams of protein per day, and adolescent girls need 65 grams of protein per day by eating fortified, fortified, or modified foods that contain high-protein ingredients. Snakehead fish (Channa striata), including freshwater fish, includes relatively high protein and complete essential amino acids. This study aimed to analyze the sensory characteristics and nutritional value of Sambal Seruit made from snakehead fish. The method of this study used experiments where snakehead fish, a local food, was added to produce the most popular harpoon. The treatment was a complete randomized block design (RCD) with three replications. Observations included sensory tests of color, smell, texture, taste, and general acceptance using hedonic and proximate test methods. The data analysis shows the evaluation results in the form of tables and graphs for the mean of each Sambal composition: Snakehead F1 (30%:70%), F2 (40%:60%), F3 (50%:50%)—The acceptance of panelists based on the Likert scale of color value. Panelists prefer Formula 2, Formula 2 based on aroma value, and Formula 3 based on taste. The proportion of snakehead fish in the seruit chili sauce formula, the higher it is, the higher the nutritional value of the seruit chili sauce.